Boundary behavior of ring Q-homeomorphisms on Riemannian manifolds - Afanas'eva, E. S. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We study the problems of a continuous and homeomorphic extension of so-called ring Q-homeomorphisms between domains on Riemannian manifolds to the boundary. We establish conditions for a function Q(x) and the boundaries of domains under which every ring Q-homeomorphism admits a continuous or homeomorphic extension to the boundary. This theory can be applied, in particular, to Sobolev classes.